Overview of Glycemic Control in Workers with Diabetes at An Occupational Clinic in Jakarta - Edwin Halim; Em Yunir; Amilya Agustina; Astrid Sulistomo; Levina Chandra Khoe (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Introduction: Based on Indonesia’s population data in 2018 and International Diabetes Federation in 2019, an estimated 1 in every 10 Indonesian workers have type 2 diabetes mellitus (T2DM). Diabetes is a chronic illness with costly implications, especially in working population. Workers with diabetes experience 12% reduction in productivity adjusted life years (PALY) and additional USD 467 monthly average healthcare cost. This study aims to determine glycaemic control in workers with diabetes.Methods: Cross-sectional study utilizing laboratory medical records from 2015-2021 in an occupational clinic in Jakarta’s Central Business District is performed. Data collected through accessing in-clinic laboratory and client lists’ electronic medical records, is paired with their respective anthropometric parameters stored in paper archives. Criteria of Fasting Blood Glucose (FBG), lipid profile, HbA1c and Body Mass Index (BMI) are based on PERKENI 2019. Inclusion criteria are workers with prior history of T2DM who underwent HbA1c examination.Results: 2,796 employees who underwent HbA1c examination were found; 65.8% normal, 29.6% pre-diabetic, and 4.6% exceeded T2DM cut-off. Amongst 2,796 employees, 1,322 had their FBG examined; 62% normal, 33.1% had increased fasting glucose and 5% exceeded T2DM cut-off; another 1,316 also had their lipid profile examined, in which 80.5% had dyslipidaemia. From 2015-2021, 160 employees had a history of T2DM, of which 86 had matching laboratory medical records, with 42 of those undergoing HbA1c examination. Of 42 respondents with diabetes who underwent HbA1c examinations, 54.8% had sub-optimal glycaemic control. FBG is the only risk factor significantly correlated to optimal glycaemic control (p <0.05).Conclusion: Health programs and policies in the workplace enacted by management and health institutions who offer medical services may play a vital role in the improvement of prevention and intervention of diabetes amongst workers.